First report of Impatiens necrotic spot orthotospovirus infecting Tulbaghia violacia Harv. in China - Hu, Jingyu (Plant disease, 2022)
Tulbaghia violacea Harv. indigenous to southern African countries, is an herbaceous perennial bulbous plant belonging to the family Amaryllidaceae. It is a popular garden plant in China. This attractive plant is traditionally used as medicine and repellent (Kubec et al. 2002; Moodley et al. 2015). In June 2021, T. violacea plants showing typical tospovirus-like symptoms of chlorotic rings patterns, were found at the campus of Yunnan University of Chinese Medicine (Fig.S1). Disease incidence was about 11.0% during the field survey. Total RNA was extracted from symptomatic leaves of T. violacea plants using the TRIzol reagent (ambio, Carlsbad, CA). Reverse transcription (RT)-PCR was conducted to identify the virus using RNA extract as the template. The degenerate primers (dTospo-F2 and dTospo-R2) (Huang et al. 2018) were used to amplify the conserved regions of the orthotospoviral L RNA sequences. No amplification was obtained from extracts of two asymptomatic plants. The amplicons from four symptomatic samples were cloned into the pMD19-T vector (TaKaRa) and sequenced (three clones for each amplicon) by Tsingke (Shanghai, China). The obtained DNA fragments were determined to be 312 bp. The sequences from four symptomatic samples were identical (GenBank acc.no. OK258285) and shared the highest nucleotide identities (98.0%) with a corresponding sequence of segment L of impatiens necrotic spot virus (INSV) isolated (GQ336991) from Phalaenopsis amabilis in Yunnan province, China. To further confirm the INSV infection to T. violacea, the samples were analyzed with the specific primers for the N, NSs and NSm genes of INSV (Table S1), respectively. Amplicons of the expected size, 789 bp, 1344 bp and 912 bp, were produced, respectively. Amplicons were cloned and sequenced. The 789-bp N (ON529554) and 1344-bp NSs (ON529554) gene sequences had 99.1% and 99.3% nucleotide identities with the corresponding region of previously described INSV Phalenopsis isolate (GQ336989), respectively. The 912-bp NSm (ON529553) gene sequence shared 99.5% nucleotide identity with the corresponding region of INSV Phalenopsis isolate (GQ336990). Metavirome and Sanger sequencing were used to complete the genome of INSV from T. violacea. The leaves of the symptomatic sample were used to construct an rRNA-depleted library using Nextera XT reagents (Illumina, San Diego, CA). The library was subjected to RNA-Seq a NovaSeq 6000 platform (Illumina, San Diego, CA). A total of 33,193,233 quality-filtered reads were obtained using BBMAP (https://github.com/BioInfoTools/BBMapBBMap - Bushnell B. - sourceforge.net/projects/bbmap/). Among 161052 reads mapped to virus sequences, 151407 reads (read ratios 94.0%) were mapped to INSV. Three complete segments of INSV genome were determined to 8,778 nt (L segment, Acc. No. ON529552), 4,958 nt (M segment, Acc. No. ON529553), and 2,983 nt (S segment, Acc. No. ON529554) in length. These segments were validated by RT-PCR and Sanger sequencing. Three segments share nucleotide sequence identities of 99.6%, 99.3% and 98.9% with the L (GQ336991), M (GQ336990) and S segments (GQ336989) of INSV Phalenopsis isolate, respectively. The results of sequence comparisons showed no evidence of reassortment between INSV and another orthotospovirus. There was a report of tomato spotted wilt virus infecting T. violacea in Florida, USA (Dey et al. 2019). No other virus infecting T. violacea was reported. INSV has been reported to infect several economically important crops including Phalenopsis, pepper etc. in China (Chen et al. 2016). INSV-infected T. violacea not only losses landscaping value but also plays an important intermedia host role in the spread of INSV. Additional surveys and evaluation will be needed to understand the potential medicinal effect of this virus on this plant. To our knowledge, this is first report of INSV in T. violacea